Evaluation of Seed Propagation and Early Growth Rates of Ocimum Gratissimum (Shrubby Basil) as Affected by Different Growth Media - I. A, Kareem (European Journal of Applied Sciences, 2021)
Variations in seedling emergence and morphological indices of Ocimum gratissimum (shrubby basil/scent leaf) seedlings in three soil types were evaluated sequel to the fact that some people believe that it is difficult to propagate it from its seeds and thereby relying on this plant that develop through dispersal despite its multiple benefits. This plant is shrubby and often utilized for culinary and other numerous medicinal purposes. The study was carried out in the Screen House of the Department of Plant Science and Biotechnology, Adekunle Ajasin University, Akungba - Akoko, Ondo State, Nigeria. Viable seeds of Ocimum gratissimum were obtained from Akungba – Akoko and the different soil types (washed river sand, sandy soil and sandy loam) used were procured from the University premises and analyzed by employing standard laboratory procedures. The experimental design used was a completely randomized design consisting of 3 treatments and 5 replicates. Analyzed soil samples (treatments) showed that sandy loam had the highest nutrient status and washed river sand was the lowest especially with regard to organic matter, %Nitrogen and available Phosphorus. The study lasted for 13 weeks and data obtained were analyzed using SPSS software package (version 20.0). Results indicated that seedling emergence commenced at the 4th day after sowing in all the treatments but washed river sand had the highest SE percentage (7th day after sowing) with significant difference (at P<0.05). Conversely, sandy loam had the highest values in all the morphological growth indices (significant at P<0.05) owing to its higher nutrient status. Thus, sandy loam was recommended for large scale production of the seedlings of this plant for its culinary and numerous medicinal uses.